22q11.2 deletion syndrome as a risk factor for aortic root dilation in tetralogy of Fallot. (10th April 2013) - John, Anitha S.; Rychik, Jack; Khan, Munziba; Yang, Wei; Goldmuntz, Elizabeth
Abstract: Background : Aortic root dilation has been observed in some patients with tetralogy of Fallot. This study examines whether 22q11.2 deletion is a risk factor for aortic root dilation in tetralogy of Fallot. Methods : Patients with tetralogy of Fallot, in the age group of 6–18 years, with defined deletion status and echocardiograms (2003–2009) were identified from research databases. The diameter at the aortic annulus, sinus, and sinotubular junction was measured and analysed as Z -scores. Variables were examined in univariate and multivariate regression analysis. Results : Of 171 patients, 66% were male, 16% had 22q11.2 deletion, 40% had an aortic arch anomaly, and 11% had both a 22q11.2 deletion and aortic arch anomaly. Echocardiograms were performed at a mean age of 12 + 3 years. More patients with 22q11.2 deletion had Z -scores >3 at the sinus diameter (45% versus 35%, p = 0.02). In the multivariate analysis, the combination of 22q11.2 deletion and aortic arch anomalies was associated with both aortic annular dilation (p = 0.006) and aortic sinus dilation (p = 0.05). In the subset with pulmonary valve atresia, similar findings were observed at the aortic annulus ( Z -score of 4.6 versus 2.2, p = 0.05) and the sinuses ( Z -score of 4.4 versus 2.7, p = 0.06). Male sex (p < 0.03) and pulmonary atresia (p < 0.006) were additional risk factors for dilation at the annulus and sinuses. Conclusions : Children with tetralogy of Fallot with 22q11.2 deletion and aortic arch anomalies have increased aortic annular and aortic sinus dilation. Further longitudinal study is needed to assess whether both features are associated with progressive aortic root dilation.